Istisna financing as practiced in Malaysia and related issues / Ibtisam @ Ilyana Ilias - Ibtisam @ Ilyana, Ilias (2007)
At present, Islamic banking in Malaysia has become very significant in catering to the needs of Muslims in getting Sharl'ah-compliant financing. In the construction and manufacturing sectors, isti~nii ' contract is deemed the most appropriate. Nevertheless, its application has been altered to suit the modern financing requirements. In so doing, several original principles of this type of sale contract have also been modified resulting in differences of opinion among international Muslim scholars as to its validity. Hence, this dissertation intends to study the original principles of isti~nii ' contract, its current application in Malaysia and also relevant issues regarding its application especially in term of its conformity to Sharf' ah principles.